1997
DOI: 10.1523/jneurosci.17-14-05271.1997
|View full text |Cite
|
Sign up to set email alerts
|

A Postsynaptic Interaction between Dopamine D1and NMDA Receptors Promotes Presynaptic Inhibition in the Rat Nucleus Accumbens via Adenosine Release

Abstract: The mechanism underlying dopamine D 1 receptor-mediated attenuation of glutamatergic synaptic input to nucleus accumbens (NAcc) neurons was investigated in slices of rat forebrain, using whole-cell patch-clamp recording. The depression by dopamine of EPSCs evoked by single-shock cortical stimulation was stimulus-dependent. Synaptic activation of NMDA-type glutamate receptors was critical for this effect, because dopamine-induced EPSC depressions were blocked by the competitive NMDA receptor antagonist D/L-2-am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
122
2
3

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(141 citation statements)
references
References 59 publications
14
122
2
3
Order By: Relevance
“…In the nucleus accumbens, most studies report that DA attenuates corticoaccumbal glutamatergic input by acting on D1-class receptors [6]. This attenuation, according to one proposed mechanism, is mediated by an inhibitory feedback action of adenosine, liberated following facilitation of NMDARs by D1-mediated PKC activation in postsynaptic neurons [58] layer PFC synapses and hippocampal-PFC synapses, agonists of D1-class receptors facilitated, whereas antagonists impaired, NMDAR-dependent LTP via cAMP-dependent mechanisms [63][64]. Acting at both D1-and D2-class receptors, DA at high concentrations facilitates LTD, whereas at low concentrations promotes LTP [65].…”
Section: Functional Evidencementioning
confidence: 99%
See 1 more Smart Citation
“…In the nucleus accumbens, most studies report that DA attenuates corticoaccumbal glutamatergic input by acting on D1-class receptors [6]. This attenuation, according to one proposed mechanism, is mediated by an inhibitory feedback action of adenosine, liberated following facilitation of NMDARs by D1-mediated PKC activation in postsynaptic neurons [58] layer PFC synapses and hippocampal-PFC synapses, agonists of D1-class receptors facilitated, whereas antagonists impaired, NMDAR-dependent LTP via cAMP-dependent mechanisms [63][64]. Acting at both D1-and D2-class receptors, DA at high concentrations facilitates LTD, whereas at low concentrations promotes LTP [65].…”
Section: Functional Evidencementioning
confidence: 99%
“…In the nucleus accumbens, most studies report that DA attenuates corticoaccumbal glutamatergic input by acting on D1-class receptors [6]. This attenuation, according to one proposed mechanism, is mediated by an inhibitory feedback action of adenosine, liberated following facilitation of NMDARs by D1-mediated PKC activation in postsynaptic neurons [58]. However, this view remains controversial [59].…”
Section: Functional Evidencementioning
confidence: 99%
“…Тормозные процессы, инициируемые этим нуклеозидом, реализуются с вовлечением и других нейромедиаторных систем. Так, активация пресинаптических А 1 -рецепторов сопровождается угнетением экзоцитоза глутаминовой кислоты и развитием тормозных процессов в ЦНС [70].…”
Section: отрезвляющие средства модулирующие систему аденозинаunclassified
“…По-видимому, активация аденозиновых рецепторов при экспозициях к этанолу сопровождается модуляцией и других нейромедиаторных систем, общим итогом которой является развитие седативного действия [70,73].…”
Section: отрезвляющие средства модулирующие систему аденозинаunclassified
“…First, even when these indirect pathways are blocked in other bram regions, KA does not produce a potentiation of elPSC amplitude. Second, both GABAB and adenosine receptor modulation of GABAergic synaptic transmission have been demonstrated in the NAcc (Uchimura and North, 1990;Tao et al 1996;Harvey and Lacey 1997;and Steffensen et al 2000). However, pretreatment with antagonists for both of these receptor systems (SCH 50911; and theophylline; GABAB and adenosine receptor antagonists, respectively) had no effect on the KA receptor-mediated potentiation of elPSCs observed in the current study (data not shown).…”
Section: Kainate Receptors In the Nucleus Accumbens Core 14mentioning
confidence: 99%